2021
DOI: 10.3390/en15010178
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the Methane Content of Coal Seams Based on Drill Cutting and Core Samples from Coal Mine Roadway

Abstract: The determination of methane content of coal seams is conducted in hard coal mines in order to assess the state of methane hazard but also to evaluate gas resources in the deposit. In the world’s mining industry, natural gas content in coal determination is usually based on direct methods. It remains the basic method in Poland as well. An important element in the determination procedure is the gas loss that occurs while collecting a sample for testing in underground conditions. In the method developed by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Figure 3 shows the underground mining gallery in the coal layer crossing the vertical well, and the laboratory tests on the Pastora layer coal samples. A new methodology to avoid gas loss while samples are collected by drill cutting was developed by [25]. The coal properties used in this study are shown in Table 1.…”
Section: Zone 1 Analysis Coalbedmentioning
confidence: 99%
“…Figure 3 shows the underground mining gallery in the coal layer crossing the vertical well, and the laboratory tests on the Pastora layer coal samples. A new methodology to avoid gas loss while samples are collected by drill cutting was developed by [25]. The coal properties used in this study are shown in Table 1.…”
Section: Zone 1 Analysis Coalbedmentioning
confidence: 99%
“…Coal seam gas content is a key parameter in the exploration and development of coalbed methane resources, which can effectively predict the occurrence of protrusion, examine the effectiveness of regional antisurge, and evaluate the degree of coal mine gas hazard. The methods of coal bed gas content determination are divided into direct method and indirect method. , The process of the indirect method to determine coal seam gas content is complicated, the measurement period is long, and the success rate is low, so the direct method is mostly used to measure coal seam gas content underground in China. The direct method of measuring coal seam gas content mainly includes three parts: determination of gas desorption in underground coal samples, determination of residual gas in a laboratory, and extrapolation of gas loss during sampling, of which the first two parts can be measured according to relevant requirements, and the results are real and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…The desorption and residual can be accurately determined in the laboratory, while the loss can only be calculated by some theoretical methods, and the calculation consequences will directly dominate the accuracy of the gas content. The sampling method has a significant impact on the loss determination results . The larger the particle size is, the smaller the loss is .…”
Section: Introductionmentioning
confidence: 99%
“…The sampling method has a significant impact on the loss determination results. 7 The larger the particle size is, the smaller the loss is. 8 The traditional loss calculation method is based on the law of gas desorption under normal pressure, 9 which is contradictory to the positive pressure sampling environment in engineering applications, and hence, this method is prone to leading to excessive error in both theory and practical applications.…”
Section: Introductionmentioning
confidence: 99%